The philosophical ideas of Swami Abhedananda: a critical study; a guide to the complete works of Swami Abhedananda - Prajnanananda, Swami, 1907- (Ramakrishna Vedanta Math, 1971)
On the philosophy of the Hindu spiritual leader Swami Abhedananda, 1866-1939, disciple of Ramakrishna, 1836-1886.